Genetic characterization of emerging PRRSV in US: new features of -2/-1 ribosome frameshifting in nsp2 region - Yan, Xingyu (Kansas State University, 2019)
Recent emergence of PRRSV variants caused increased mortality in growing pigs and reproductive failure in sows. In this study, we characterized two emerging PRRSV variants isolated from infected pigs. Genome sequencing analysis showed that KS 17-C1 and KS 17-C2 have GP5 RFLP cutting pattern of 1-7-4 and 1-18-2, respectively; and they belong to two distinct phylogenetic clades, in which each associated with a group of emerging PRRSV strains that were reported from pigs with severe clinical manifestations. Further in-depth sequence analysis revealed that the -2/-1 programmed ribosome frameshifting (PRF) signal located within nsp2 is the region where these viruses differ the most from historical PRRSV strains. Our previous studies demonstrated that -2/-1 PRF generates two frameshifting products, nsp2TF and nsp2N. In the genome of historical PRRSV strains, the -1 PRF immediately encounters a stop codon, which terminates the translation of -1 reading frame to produce nsp2N. However, KS 17-C1 and KS 17-C2 isolates contain mutations disrupting the -1 PRF stop codon; therefore, extending the translation of nsp2N to generate additional 16 or 23 amino acids at 3’-end (nsp2N+16aa, nsp2N+23aa). The emergence of -1 PRF stop codon mutants was traced back in PRRSV sequences published in the Genbank since 2011 and percentage of the mutants has quickly increased afterward (up to 69% of the sequences). More importantly, these -1 PRF stop codon mutants were reported from swine farms experiencing PRRSV outbreaks with increased mortality/morbidity. To determine whether nsp2N extension correlates with the increased pathogenicity of these viruses, recombinant virus with restored -1 PRF stop codon was generated and compared with wild-type virus. Results showed that the mutant with restored -1 PRF stop codon induced higher levels of innate immune response, suggesting a possible link between nsp2N extension and pathogenicity of this group of newly emerging PRRSV variants in the US.
Keywords: Emerging disease; PRF; nsp2; PathogenesisPRRSV